Joseph Conrad's Heart of darkness - Kuper, Peter 1958- (W.W. Norton & Company, 2020)
"Acclaimed cartoonist Peter Kuper delivers a powerful interpretation of this controversial classic. Heart of Darkness has unsettled generations of readers with its haunting portrait of colonialism and brutal exploitation in Africa. Now award-winning illustrator Peter Kuper reimagines Conrad's masterpiece for a new generation, transforming this dramatic tale of madness, greed, and evil into something visually immersive and profoundly complex. Drawn in pen, black pencil, and ink wash reminiscent of the etchings and lithography of Francisco Goya and Honoré Daumier, Kuper's Heart of Darkness captures the ominous atmosphere and tempo of Charles Marlow's journey up the River Congo. Kuper's images and concise text confront Conrad's colonial attitudes and systemic racism yet leave room for readers to engage with these issues on their own terms. Longtime admirers of the novella will appreciate Kuper's innovative interpretations and see Conrad's opus with fresh eyes, while new readers will discover a brilliant introduction to a canonical work of twentieth- century literature"--
Keywords: Conrad, Joseph -- 1857-1924 -- Heart of darkness; Conrad, Joseph / 1857-1924 / Heart of darkness / Adaptations; Europeans / Africa / Comic books, strips, etc; Trading posts / Comic books, strips, etc; Imperialism / Comic books, strips, etc